Gifted student in the reality of the polish school - Agnieszka Bochniarz; Anna Grabowiec (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
The potential of gifted people is a significant resource for every community. That is why it is important that all of the participants of educational process are aware of the categories "abilities" and "gifted student" and their value. The article presents the issues in working with gifted students. The initial part introduces the term and characteristics of a gifted student and draws the attention to the underachievement syndrome in gifted students and asynchronous development. The role and assignments of school are indicated and special support this institution should provide gifted students with. The article also presents the results of research concerning attention to gifted children in polish schools. Finally, the examples of "good practices" which support the measures taken by schools to plan the education of gifted students are presented.